Prostaglandins for management of retained Placenta (A Systematic Review of Randomised Trials) (2012)
La retención de placenta afecta del 0.5 al 3% de las mujeres en el puerperio y constituye la mayor causa de mortalidad maternal debida a hemorragia postparto. Habitualmente, la retención de la placenta ha sido manejada con remoción manual o curetaje bajo anestesia. El objetivo de la presente revisión sistemática fue evaluar la efectividad y la seguridad de las prostaglandinas para el manejo médico de la placenta retenida. Se recuperaron 13016 referencias, de las cuales 3 fueron incluidas en esta revisión sistemática con meta-análisis. El uso de prostaglandinas se asoció a una mayor tasa de expulsión de la placenta sin remoción manual (RR 2.53 95% CI 1.66 to 3.86) y a un menor tiempo para expulsión de la placenta (MD -6.50 95% CI -11.19 to -1.81). Las prostaglandinas podrían ser una intervención efectiva para facilitar la expulsión de la placenta pero la calidad de la evidencia es limitada. No podemos recomendar ningún cambio en la práctica clínica. / Abstract. Retained placenta affects 0.5%–3% of women following delivery and is a major cause of maternal death due to postpartum haemorrhage. Usually, the retained placenta has been managed by manual removal or curettage under anaesthesia. The objective of this systematic review was to assess the effects and safety of prostaglandins for management of retained placenta. A total of 13016 references were retrieved and finally 3 three studies were included in this systematic review with meta-analyses. Prostaglandins showed higher rate of expulsion of the placenta without manual removal (RR 2.53 95% CI 1.66 to 3.86) and a lower time for delivery of the placenta (MD -6.50 95% CI -11.19 to -1.81). Prostaglandins might be an effective intervention to facilitate the delivery of the retained placenta, but we have very little confidence in the effect estimate. We can not recommend any change in clinical practice until have high quality evidence.